До формування понятійного апарату теорії інновацій - Ковчуга, Л.І. (Економічний вісник Донбасу, 2017)
У статті досліджено понятійний апарат теорії інновацій. Виокремлено властиві інноваціям ознаки, розглянуто співвідношення споріднених до інновації понять - «новації» та «нововведення». Визначено, що, незважаючи на поширеність, поняття«інновація» дотепер не має однозначного визначення. Для впорядкування термінології та формування цілісного уявлення про інновації здійснено систематизацію підходів до їх трактування. Визначено обмеженість та однобічність сприйняття інновацій з позиції перших двох і переваги третього, що дозволило обґрунтувати відмінності між інновацією та інноваційною діяльністю та надати специфічне визначення поняттю «активізація інноваційної діяльності підприємства». Розроблено науково-методичний підхід до типології інновацій, в основу якого покладено матричний принцип побудови, залежно від повноти охоплення етапів інноваційної діяльності підприємства і типів інновацій за різними класифікаційними ознаками: за ефектом впливу на ринок, розвиток галузей та умови конкуренції між підприємствами; за стратегією розвитку підприємства; за походженням; за джерелом конкурентної переваги. В статье исследован понятийный аппарат теории инноваций. Выделены присущие инновациям признаки, рассмотрено соотношение родственных инновациям понятий - «новации» и «нововведения». Определено, что, несмотря на распространенность, понятие «инновация» до сих пор не имеет однозначного определения. Для упорядочения терминологии и формирования целостного представления об инновациях осуществлена систематизация подходов к их трактовке. Определены ограниченность и односторонность восприятия инноваций с позиции первых двух и преимущества третьего, что позволило обосновать различия между инновацией и инновационной деятельностью и дать специфическое определение понятию «активизация инновационной деятельности предприятия». Разработан научно-методический подход к типологии инноваций, в основу которого положен матричный принцип построения, в зависимости от полноты охвата этапов инновационной деятельности предприятия и типов инноваций по различным классификационным признакам: по эффекту воздействия на рынок, развитие отраслей и условия конкуренции между предприятиями; по стратегии развития предприятия; по происхождению; по источнику конкурентного преимущества. The article investigations of the conceptual framework of the theory of innovation. Innovations in the system of related concepts are considered. It is defined that to transform «novation» to the form of innovation, it is necessary to fulfil a number of conditions: to invest, to conduct marketing research, to prepare the manufacture for the output of new products, to carry out the manufacturing, to sell products. The signs of innovation are highlighted, they are the novelty, commercialization, distribution (diffusion), unpredictability, riskiness, investment needs, which showed the complexity and multidimensionality of the innovation’s phenomenon. It is determined that, despite the prevalence, the concept of«innovation» still doesn’t have the unambiguous definition. To harmonizing terminology and form a holistic view of innovation, the systematization of approaches to their interpretation has been carried out. It is identified the limitations and unilateralism of the perception of innovation from the position of the first two approaches and the advantages of the third one. The differences between innovation and innovation activity are substantiated and a specific definition of the concept of «activation of the firm's innovation activity» is given. A scientific-methodical approach to the typology of innovations is developed. The approach is based on the matrix principle, depending on the completeness of coverage of the stages of innovation activity of the enterprise and the types of innovations according to different classification criteria: the effect of the impact on the market, the development of industries and the conditions of competition between enterprises; on the strategy of enterprise development; by origin; by source of competitive advantage.